THE INFLUENCE OF INCOME LEVEL, PROMOTIONS, SERVICE QUALITY, LOCATION ON CUSTOMERS' SAVING DECISIONS AT BANK SYARIAH INDONESIA KCP PANDAAN - Erwan Aristyanto; Tommy Wahyu Budisentoso (WORLDVIEW ( Development economic and sharia studies journal ), 2022)
This research is entitled "The Influence of Income Level, Promotion, Service Quality, Location on Customers' Decisions to Save at Indonesian Sharia Bank KCP Pandaan". The aim of this research is to examine the influence of income level, promotion, service quality, location on customer decisions partially and simultaneously. The number of samples taken in this research was 50 customers as respondents. The data was tested using validity and reliability tests carried out using IBM SPSS Statistics Version 22 software. The analysis test used in this research was the factor analysis test. The results of this research analysis show that the factors that influence customers' decisions to save at Bank Syariah Indonesia KCP Pandaan are influenced by income level (X1), promotion (X2), service quality (X3), location (X4). These four factors individually and together have a significant influence on customers' decisions to save at Bank Syariah Indonesia KCP Pandaan.